A Night (of the World) at the Opera: History and Excess in Opera’s Second Death - Alberto Toscano (EJP import test, 2021)
Summary: This essay revisits Mladen Dolar and Slavoj Žižek’s book Opera’s Second Death, exploring the figure of history that arises from their joint intent to, as Adorno once put it apropos of Wagner, realize the fractures that traverse the opera-form. In particular, the essay homes in on the conceptual manoeuvres whereby Dolar and Žižek’s limn opera’s elective affinities with a psychoanalytic theory of the subject, paying special attention to the ways in which operatic incarnations of voice and femininity stage a thinking of excess with striking political overtones.[1] Dolar’s contribution to this co-authored work explores a fracture within history – revealing Mozart’s operas as the dramatic site for the antinomies of Enlightenment subjectivity in its sexual and political dimensions, as they emerge in the revolutionary transition between two epochs. Žižek’s study of Wagner, in a complementary, which is to say dialectical way, lays bare the fracture of subjectivity itself – in the guise of the asymmetrical difference between sexual positions, but above all in the feminine figure of excess that is so central to opera. It is from this double fracture that this essay tries to reconstruct a psychoanalytic interrogation of how history cuts through the subject and resonates in the voice.
Keywords: femininity; history; Opera; Psychoanalysis; Theory of the subject; voice